Pengendalian Alih Fungsi Lahan Pertanian Untuk Perumahan - Wirda Moliju (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Control over the conversion of agricultural land to housing is a complex and important issue in urban development. The purpose of this study is to examine further regarding the Control of Conversion of Agricultural Land Functions for Housing. This research method is the study of literature. Literature study research is a research method that aims to analyze and evaluate existing literature. The conversion of agricultural land can threaten food availability and increase dependence on food imports. Good spatial planning is the key to controlling the conversion of agricultural land. Clear and detailed policies are needed to regulate land use effectively and take into account housing needs and agricultural potential.